Opportunities for Informatics to Improve Discharge Planning: A Systematic Review of the Literature - Archie, Rhonda Renee (American Medical Informatics Association, 2009)
The discharge planning process can be successful when information is shared among the patient, caregiver, and provider from admission through post discharge. The objective of this paper was to evaluate the association of information sharing among patients, caregivers, and health care providers and the impact on the discharge process. The authors identified reports of the discharge planning process through systematic electronic database searches. The eligibility criteria were 1) usual discharge planning process, and 2) patient, caregiver, or provider perception or feedback. Of the eligible articles, all voiced concern about a broken discharge planning process that affected the information exchanged among all involved in patient care. Outcomes related to satisfaction, knowledge transfer, and communication were identified. The initial evidence suggests information sharing through interdisciplinary patient care can play a significant role in the future.